Current Research Directions in Regenerative Therapy - Bhagyashree Lenka1 , Rinkee Mohanty2 , Rashmita Nayak3, Gatha Mohanty4 , Anurag Satpathy3 , Sourav P (Indian Journal of Forensic Medicine & Toxicology, 2020)
Chronic periodontitis has been the principal cause behind the irreparable destruction of the periodontium. Inthe field of surgical periodontal therapy, regeneration of damaged tissues by utilizing our body’s naturallyproduced growth factors along with various other biomaterials either synthetically formulated or animallyderived has piqued the attention of the dental practitioner. The human body has a natural capacity andpotency of regenerating the lost tissue up to an extent; this characteristic is tapped in the regenerativetherapy. Presently this therapy is bounded by the limited research and knowledge on the materials that can beused, instruments that are required for a successful procedure and method devised to gain desired outcomespresently available and the body’s natural capability for regeneration. Tissue engineering use of stem cell,gene therapy and research on various aspects of regenerative therapy, has produced predicted results inexciting new treatment method for clinicians shortly. Traditional treatment modalities like mechanicalinstrumentation, curettage and open flap debridement result in keeping the inflammation in check andlong junctional epithelium formation which leads to only periodontal repair and not regeneration. Manypractitioners frequently use a combined method of putting both barrier membrane and bone grafts to curbthe limitations posed by the down growth of epithelium and sagging of the non-rigid barrier used to maintainthe grafts in place. This has led to enhanced interest in the Hence, there has been increased attention in thetreatment of chronic diseases of the periodontium further elevating the quality of life of the patients. Thisreview article aims to review diverse obtainable bio-materials, scaffolds, barriers and osseous grafts alongwith the plethora of procedures applied in periodontal regenerative therapy.